2020
DOI: 10.1039/c9pp00406h
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence characteristics of lipofuscin fluorophores from human retinal pigment epithelium

Abstract: Lipofuscin granules accumulate in the retinal pigment epithelium (RPE) with age, especially in patients with visual diseases, including progressive age-related macular degeneration (AMD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…Our results on photooxidation of isolated RPE lipofuscin (Fig. 1F) are consistent with the results of a comparison of fluorescence emission spectra recorded in suspension of human RPE cells isolated from 74 year old eyes affected with AMD and 75 year old eyes without any signs of AMD [63,91]. The fluorescence spectra from the AMD-affected RPE cells obtained with excitation with 488 nm light show that the emission ratio at 550 nm to 600 nm is increased when compared with normal RPE of similar age.…”
Section: Decrease In Long-wavelength Fluorescence During Photooxidation Of Lipofuscin and An Increase In Blue/cyan Or Green To Orange Flusupporting
confidence: 90%
See 1 more Smart Citation
“…Our results on photooxidation of isolated RPE lipofuscin (Fig. 1F) are consistent with the results of a comparison of fluorescence emission spectra recorded in suspension of human RPE cells isolated from 74 year old eyes affected with AMD and 75 year old eyes without any signs of AMD [63,91]. The fluorescence spectra from the AMD-affected RPE cells obtained with excitation with 488 nm light show that the emission ratio at 550 nm to 600 nm is increased when compared with normal RPE of similar age.…”
Section: Decrease In Long-wavelength Fluorescence During Photooxidation Of Lipofuscin and An Increase In Blue/cyan Or Green To Orange Flusupporting
confidence: 90%
“…Similar but less pronounced changes could be seen for emission at 550 nm. We were interested in fluorescence changes at that wavelength because it has been reported that the ratio of fluorescence intensity at 550 nm to 600 nm is increased in RPE cells from eyes affected by age-related macular degeneration (AMD) in comparison with RPE cells isolated from healthy eyes of similar age [63]. The fluorescence was induced by excitation with 488 nm light.…”
Section: Exposure Of Rpe Lipofuscin To Visible Light Results In a Decrease Of Longwavelength Fluorescence And An Increase In The Short-wamentioning
confidence: 99%
“…However, the overwhelming density of brightly autofluorescent debris, such as lipofuscin found near the pial surface, were sometimes detected as false positives by Seg-CNN (Supplementary Figure 3B). We suggest that researchers using this software avoid areas with dense debris or lipofuscin, or at least exclude these regions from analysis, although this can be difficult when imaging in aged tissue (Moreno-García et al, 2018; A. Yakovleva et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…We suggest that researchers using this software avoid areas with dense debris or lipofuscin, or at least exclude these regions from analysis, although this can be difficult when imaging in aged tissue (Moreno-García et al, 2018;A. Yakovleva et al, 2020).…”
Section: Cnn-based Analysis Retains Tracking Ability Despite Changes In Image Qualitymentioning
confidence: 99%
“…Lipofuscin (LF) is a cellular metabolic by-product resulting from incomplete lysosomal degradation of shed photoreceptor outer segments by the RPE and represent the primary substance imaged with short-wavelength autofluorescence (SW-AF). [3] At the start of phototransduction, 11cis-retinal chromophore of rhodopsin absorbs a photon of light and isomerizes to all-transretinaldehyde [Figure 1]. This form may be released from the activated rhodopsin and react with phosphatidylethanolamine (PE), also in the disc membrane, to form N-retinylidene-PE (NRPE).…”
Section: Fundamentals Of Autofluorescence Molecular Originmentioning
confidence: 99%